Book Review: Ensayos de historia intelectual, by Mario Oliva Medina - Devés-Valdés, Eduardo (2020)
The book examined here has as principal themes the relationship between intellectuals, social movements and politics. The currents of anarchism and communism and their roles in the history of Costa Rican ideas are analyzed in the essays that compose this book, in addition of local intellectual movements of their own, such as unionism. The place of journals on intellectual history is also discussed, since they compose the medium in which an intellectual ecosystem is developed, and its evolution is examined in detail in the essays that are present in the text reviewed here. Lastly, the text strives in standing out the relevance of lesser-known intellectual figures.